Serum nitric oxide in liver cirrhosis and its relation to blood pressure - Ersin AKARSU; Nihat OKÇU; Kenan AKGÖZ; İlhami KİKİ; Ahmet KIZILTUNÇ; Mehmet GÜNDOĞDU (Turkish Journal of Gastroenterology, 2019)
-